2002
DOI: 10.1124/jpet.300.2.668
|View full text |Cite
|
Sign up to set email alerts
|

Tenidap, an Anti-Inflammatory Agent, Inhibits DNA and Collagen Syntheses, Depresses Cell Proliferation, and Lowers Intracellular pH in Cultured Human Gingival Fibroblasts

Abstract: The effect of tenidap [(Ϯ)-5-chloro-2,3-dihydro-3-(hydroxy-2-thienylmethylene)-2-oxo-1H-indole- 3 H]proline incorporation at a concentration greater than 50 M on the 4th day and at more than 20 M on the 8th day of treatment. The presence of 1 M nifedipine or 1 M nicardipine did not alter the depressing effect of tenidap. Tenidap (20 M) also lowered intracellular pH. These results suggest that tenidap might be effective for the prevention of gingival overgrowth caused by calcium channel blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Pulmonary stretch receptors (PSRs) became more active with increasing lung volume V (membrane bias = 0.5 V mV/%VC) and mediated the Hering–Breuer reflex. Deflation-sensitive lung receptors were also implemented (Paintal, 1955; Luck, 1970; Wei and Shen, 1985; Iscoe and Gordon, 1992; Bergren and Peterson, 1993; Matsumoto et al, 2002; Yu et al, 2003). A low threshold population (Def_1, membrane bias = − 0.225( V  − 70) mV/%VC) and its afferent pathway introduced in Poliaček et al (2011) was used to represent a class of possible network mechanisms for generating an inhibitory bias on E-Dec neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary stretch receptors (PSRs) became more active with increasing lung volume V (membrane bias = 0.5 V mV/%VC) and mediated the Hering–Breuer reflex. Deflation-sensitive lung receptors were also implemented (Paintal, 1955; Luck, 1970; Wei and Shen, 1985; Iscoe and Gordon, 1992; Bergren and Peterson, 1993; Matsumoto et al, 2002; Yu et al, 2003). A low threshold population (Def_1, membrane bias = − 0.225( V  − 70) mV/%VC) and its afferent pathway introduced in Poliaček et al (2011) was used to represent a class of possible network mechanisms for generating an inhibitory bias on E-Dec neurons.…”
Section: Resultsmentioning
confidence: 99%
“…4 Decreased failure loads and increased rates of failure have also been found in surgically repaired rat supraspinatus tendons of animals given NSAIDs compared with controls. 5 In studies using in vitro cell cultures, NSAIDs have been reported to inhibit collagen synthesis in various cell types 6,7 and therefore are postulated to exert a negative impact on tissue healing.…”
mentioning
confidence: 99%
“…Hsu et al [10] reported that saikosaponin D inhibited the growth of cells in the human cancer cell line, A549. Matsumoto and Fujii [11] reported that tenidap, an anti-inflammatory agent, inhibited collagen synthesis in cultured human gingival fibroblasts. Thus, we propose that depression of both bFGF exocytosis and collagen synthesis as a result of steroidal effect of saikosaponin and glycyrrhizin in gingival fibroblasts is involved in the characteristic growth-inhibiting effect of Saireito.…”
Section: Discussionmentioning
confidence: 99%